2004
DOI: 10.1007/s00125-004-1544-y
|View full text |Cite
|
Sign up to set email alerts
|

Short-term infusion of interleukin-6 does not induce insulin resistance in vivo or impair insulin signalling in rats

Abstract: Infusion of IL-6 for 120 min in rats during euglycaemic-hyperinsulinaemic conditions did not alter the effect of insulin on whole-body glucose homeostasis, plasma adiponectin levels or insulin signalling in target tissues. Thus, the acute effects of IL-6, associated with SOCS-3 induction, do not lead to whole-body insulin resistance. These data further underscore the importance of the chronic, and potentially tissue-specific effects of IL-6 on insulin signalling and action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 56 publications
(76 reference statements)
1
32
0
Order By: Relevance
“…In contrast, an acute increase in IL-6 levels has no significant effect on serum insulin concentration in either rodents or humans in vivo (33). In fact, similar to our findings in the MKOs, short-term infusion of IL-6 does not induce insulin resistance in rats in vivo despite SOCS3 induction (36). Moreover, IL-6 knockout animals have normal insulin levels, although they develop obesity at the age of 6-7 months (33).…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, an acute increase in IL-6 levels has no significant effect on serum insulin concentration in either rodents or humans in vivo (33). In fact, similar to our findings in the MKOs, short-term infusion of IL-6 does not induce insulin resistance in rats in vivo despite SOCS3 induction (36). Moreover, IL-6 knockout animals have normal insulin levels, although they develop obesity at the age of 6-7 months (33).…”
Section: Discussionsupporting
confidence: 72%
“…Initially, we hypothesized that continuous IL-6 stimulation might induce liver injury and fibrosis, and neutralizing the Blockade of IL-6 Receptor in MCD Diet-Fed db/db Mice K Yamaguchi et al IL-6 receptor by treatment with MR16-1 would attenuate liver injury and prevent the development of NASH in MCD diet-fed db/db mice, as in wild-type mice, because previous reports showed that long-term IL-6 exposure induced SOCS3 expression, caused insulin resistance and exacerbated liver injury. [27][28][29][30] Expectedly, we found that an MCD diet induced severe NASH in db/db mice. Unexpectedly, however, this diet induced IL-6 resistance.…”
Section: Discussionmentioning
confidence: 65%
“…mRNA analyses and immunoblotting The experimental procedures have been described previously [37]. For detailed information, see ESM.…”
Section: Immunohistochemistry On Liver Sections and Flow Cytometry Anmentioning
confidence: 99%